BCLB, methylated in hepatocellular carcinoma, is a starvation stress sensor that induces apoptosis and autophagy through the AMPK-mTOR signaling cascade. (1st June 2017) - Liu, Xiaolong; Hu, Xiaotong; Kuang, Yeye; Yan, Peijian; Li, Lili; Li, Chen; Tao, Qian; Cai, Xiujun
Abstract: Epigenetic disruption of tumor suppressor genes (TSGs), particularly DNA methylation, plays a key role in hepatocellular carcinoma (HCC) pathogenesis. Through methylome study, we identified BCLB as a methylated gene in HCC. BCLB was methylated in all tumor cell lines with silenced or reduced expression. BCLB was further found to be silenced in 55.2% (58/105) of HCC samples, while 91.4% (96/105) of paired non-tumor tissues showed high BCLB expression. BCLB protein expression was significantly correlated with HBV status (p = 0.036), AFP (p = 0.048), tumor size (p = 0.006), and TNM stage (p = 0.022). The overall survival and disease-free survival rate of HCC patients with positive BCLB expression were both significantly higher than those with negative BCLB expression (p = 0.032 and 0.027, respectively). Ectopic expression of BCLB in HCC cells inhibited cell growth in vitro and in vivo . Mechanistic study showed that BCLB expression was a starvation stress sensor inducing apoptosis and autophagy simultaneously in HCC cells through the adenosine monophosphate-activated protein kinase AMPK-mTOR signaling cascade. Thus, epigenetic suppression of BCLB expression is involved in HCC development, which might have therapeutic implications for HCC patients. Highlights: BCLB as a functional tumor suppressor is frequently methylated in HCC. BCLB, a starvation stress sensor, induced apoptosis and autophagy simultaneously. BCLB as a central element of AMPK-mTOR signaling cascade role in HCC. Promoter methylation of BCLB is a potential epigenetic biomarker for HCC.